THU0485 The SPP1 Rs9138 Variant Contributes to the Severity of Radiologic Damage in Acpa-Negative Rheumatoid Arthritis: Results from the ESPOIR and Leiden EAC Cohorts. (10th June 2014) - Juge, P.-A.; Van Steenbergen, H.W.; Constantin, A.; Tobon, G.; Schaeverbeke, T.; Combe, B.; Devauchelle-Pensec, V.; Nigon, D.; van der Helm-van Mil, A.H.; Dieudé, P.
Abstract : Background: Genetic variants are estimated to contribute most to the total variance in rheumatoid arthritis (RA) joint destruction, with clinical and serologic risk factors explaining only about one-third of the total phenotypic variation. To date, most risk alleles for RA joint destruction have been identified in anti-citrullinated protein antibodies (ACPA)-positive patients or in pooled ACPA-negative and -positive patients, but little is known about the genetic contribution to ACPA-negative RA severity. Recently, we reported a significant contribution of the combination of the SPP1 rs9138 and rs11439060 functional variants to risk of RA, the magnitude of the association greater in patients with negative than positive ACPA status (1). These RA patients fulfilled the 1987 ACR revised criteria for RA, which include radiographic changes typical of RA; so ACPA-negative individuals may have joint destruction classified as RA. Consequently, we hypothesized that SPP1 variants may contribute to the severity of joint destruction in RA, specifically in ACPA-negative patients. Objectives: To investigate the association between SPP1 rs9138 and rs11439060 and the progression rate of joint damage in ACPA-negative RA patients Methods: We included 662 RA patients of the ESPOIR cohort (discovery phase) for whom radiographs of the hand and feet were obtained at the first visit and at 1- and 2-year follow-up. Patients underwent genotyping for SPP1 rs9138 and rs11439060. Association analyses were performed according to the ACPA status of patients. SPP1 variants identified to be significantly associated with the progression of joint damage were subsequently investigated in 273 ACPA-negative RA patients included in the Leiden Early Arthritis Clinic (EAC) cohort, these patients had 1, 316 sets of radiographs during 7 years follow-up (replication phase). Results: In the first cohort, SPP1 rs9138 was significantly associated with radiological progression of joint destruction over 2 years follow-up. This association was restricted to the 358 ACPA-negative patients that had a 0.93 -fold rate of joint destruction per year per minor allele as compared with the wild type ( P =0.034). In the replication phase rs4754 which is in complete linkage disequilibrium with rs9138, was associated with radiographic progression over 7 years in 273 ACPA-negative patients of the Leiden EAC (0.78-fold rate joint destruction for each minor allele at any time as compared with the wild type, p=0.005). Combined analysis of the ESPOIR and Leiden EAC cohorts revealed 0.91-fold rate of joint destruction over a 2-year follow-up ( P =0.022). Conclusions: The SPP1 rs9138 functional variant was identified and replicated to contribute to joint damage progression in ACPA-negative RA. References: Gazal S, Sacre K, Allanore Y, et al. Ann Rheum Dis Published Online First: doi:10.1136/annrheumdis-2013-204581. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2373